Antibacterial activity of 5-bromo substituted phenyl N-acylhydrazone derivatives with aromatic substitution at ortho- and para- directors as potential adjuvants - Lim Jin Yu; Sim Kooi Mow; Teo Kah Cheng (BIO Web of Conferences)
Antibiotics are frequently used in the food industry to ensure food safety and sustainability, predominantly in treating bacterial infections in food animals. Due to the massive use of antibiotics, emergence of antibiotic resistance (ABR) and multidrug resistance (MDR) threaten public health. Antibiotic adjuvants serve as an alternative strategy to combat these issues. N-acylhydrazone (NAH) has been proven to be a promising and versatile motif in drug design and medicinal chemistry due to its pronounced antimicrobial effect. Nine chemically synthesised NAH derivatives were tested for in vitro antibacterial activity against selected Gram-positive, Gram-negative and resistant strains using broth microdilution assay to determine minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The study showed that Compound 9 exhibited the highest antibacterial activity against Bacillus subtilis and Pseudomonas aeruginosa (MIC and MBC = 62.50 µg/mL) among the nine tested compounds. Furthermore, the interaction between tested compounds and streptomycin were evaluated through calculation of fractional inhibitory concentration (FIC) index. Combination of all tested compounds with streptomycin demonstrated strong to moderate inhibitory activity against all tested bacterial strains (MIC = 7.81–62.50 µg/mL), while Compounds 1 and 2 were potential adjuvants due to synergistic effect observed in combination with streptomycin against Staphylococcus aureus.